MOTIVASI GENERASI Z TERHADAP OLAHRAGA GYM DI ARENA FITNESS BANDA ACEH - Ikramul Husna; Zikrur Rahmat; Irwandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the phenomenon of increasing interest among Generation Z in gym activities as part of modern healthy lifestyle trends. The main problem in this study is to identify the factors that motivate Generation Z to perform gym exercises and to determine which factor is the most dominant at Arena Fitness Banda Aceh. The objective of this research is to describe and analyze the levels of health, physical appearance, social, and lifestyle motivations in this group. This study utilizes a quantitative descriptive approach with a survey method. The research sample consisted of 30 respondents from Generation Z selected using purposive sampling techniques. Data were collected through questionnaire instruments using a Likert scale, observations, and structured interviews. The data analysis technique employed was descriptive statistics including percentages and means. The research results based on questionnaire data show that health motivation is the most dominant factor with a percentage of 94.29% (very good category). Lifestyle motivation is also at a very strong level with a dominance in the very good category at 86.70%, followed by physical appearance motivation which reached 83.30% in the very good category. Meanwhile, social motivation has the lowest influence compared to other factors. The conclusion of this study is that Generation Z motivation for gym exercise is driven more by intrinsic factors, namely health awareness and lifestyle habituation, compared to extrinsic factors.